K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 12 2018

ai giúp e đi ạ

27 tháng 11 2022

\(=\dfrac{\left(x+y\right)^2-z^2}{\left(x+z\right)^2-y^2}=\dfrac{\left(x+y+z\right)\left(x+y-z\right)}{\left(x+z-y\right)\left(x+y+z\right)}=\dfrac{x+y-z}{x-y+z}\)

29 tháng 6 2017

Ta có: \(\left(x-y-z\right)^2\)

= \(\left[\left(x-y\right)-z\right]^2\)

= \(\left(x-y\right)^2-2\left(x-y\right)z+z^2\)

= \(x^2-2xy+y^2-2xz+2yz+z^2\)

= \(x^2+y^2+z^2-2xy+2yz-2xz\left(đpcm\right)\)

NV
12 tháng 11 2018

\(\dfrac{x^2-2xy+y^2+2z\left(x-y\right)+z^2}{\left(x-y\right)^2-z^2}=\dfrac{\left(x-y\right)^2+2z\left(x-y\right)+z^2}{\left(x-y-z\right)\left(x-y+z\right)}\)

\(=\dfrac{\left(x-y+z\right)^2}{\left(x-y-z\right)\left(x-y+z\right)}=\dfrac{x-y+z}{x-y-z}\)

26 tháng 7 2021

Trả lời:

sửa đề: \(\frac{x^2+y^2+z^2-2xy+2xz-2yz}{x^2-2xy+y^2-z^2}\)

\(=\frac{\left(x-y+z\right)^2}{\left(x-y\right)^2-z^2}=\frac{\left(x-y+z\right)^2}{\left(x-y+z\right)\left(x-y-z\right)}=\frac{x-y+z}{x-y-z}\)

9 tháng 12 2018

\(\frac{x^2+y^2+z^2-2xy+2xz-2yz}{x^2-2xy+y^2-z^2}\)

\(=\frac{\left(x-y+z\right)^2}{\left(x-y\right)^2-z^2}\)

\(=\frac{\left(x-y+z\right)^2}{\left(x-y-z\right)\left(x-y+z\right)}\)

\(=\frac{x-y+z}{x-y-z}\)